Options for the prevention of endothelial dysfunction and atherosclerotic vascular lesions in perimenopausal patients: A prospective study - Irina A. Lapina; Yulia E. Dobrokhotova; Yana A. Nikitenko; Anatoly G. Tyan; Tatiana G. Chirvon; Vladislav V. Taranov (IP Berlin A.V., 2024)
Introduction. Cardiovascular diseases are still the leading cause of death worldwide. In contrast to men, in women, cardiovascular diseases, such as coronary artery disease, acute cerebrovascular accident, and thrombosis of various localization, develop later in life. A fold rise in risk begins during the menopausal transition. Given the increase in the postmenopausal period of a woman's life, it seems interesting to search for new methods of early prevention of cardiometabolic complications already in perimenopause. Aim. To optimize early non-hormonal prevention of endothelial dysfunction and perimenopausal cardiovascular complications. Materials and methods. A prospective study included 50 patients aged 45-55 years in perimenopause without obesity and other somatic or gynecological disorders with menopausal syndrome of varying severity. Patients in group 1 (n=25) received combined non-hormonal treatment of menopausal symptoms and prevention of cardiovascular complications [sulodexide 250 lipasemic units (LU) 2 times a day + phytoestrogen (cimicifuga extract) 1 capsule 2 times a day]. In group 2 (n=25), patients received only phytoestrogen according to the same regimen. Results. After 1 year of observation, the mean thickness of the intima-media complex of the common carotid artery in group 1, in which patients received complex course therapy including sulodexide (Vessel Due F), decreased by 3.7%, and in group 2 increased by 26.8%. In group 1, it was found that after 1 year of regular use, treatment contributed to a decrease in blood fibrinogen level by 11.8% and an increase in thrombin time by 24.5%, which, in combination with a decrease in prothrombin concentration and an increase in activated partial thromboplastin time by 4.7 s, indicates a pronounced therapeutic effect on the hemostasis system. Conclusion. All markers of early atherosclerosis and vascular complications progress during postmenopause and with increasing age. However, complex protective therapy, including glycosaminoglycans sulodexide), can slow down this progression while improving patients' quality of life. Non-hormonal complex therapy can not only neutralize menopausal symptoms but also prevent long-term vascular complications caused by increasing age and the lack of estrogen-protective effect.